The relationship between head and neck posture and VDT screen height in keyboard operators. - Kietrys DM; McClure PW; Fitzgerald GK (Physical Therapy, 1998)
BACKGROUND AND PURPOSE: The purpose of this study was to determine the effect of change in video display terminal (VDT) height from desktop height (96.5 cm [38 in]) to an elevated position (109.2 cm [43 in]) on postural angles of the head and neck and the effect on cervical spine flexion moments. SUBJECTS: Twenty-seven persons (3 male, 24 female) who spent at least 3 hours per day using a computer while seated were the subjects. The subjects had a mean age of 36.7 years (SD=6.0, range=25-47). METHODS: Subjects were photographed over two 10-minute periods while seated using a computer with the VDT at two different heights. Later, a goniometer was used over images to record angles. RESULTS: There was no difference in cervical flexion moment between the two screen positions. Several postural angles of the head and neck showed changes, but the clinical relevance of these changes is questionable. CONCLUSION AND DISCUSSION: Changing the VDT height from 96.5 to 109.2 cm (floor to midscreen) has no effect on flexion moment on the cervical spine during short periods of VDT operation. If flexion moment is considered a biomechanical indicator of postural stress, it does not appear that the elevated screen position reduces postural stress on the cervical spine during short periods of VDT operation.